Gendering Trade Negotiations: Elite Spaces of Work as Regulatory Nodes in the Global Economy - Johnson, Jennifer L. (Atlantis)

(untitled) (Mount Saint Vincent University, 2013)
I argue that free trade negotiations function as a regulatory node in flows of global capital, revealing that social relations of power including gender and nationality mediate the production of elite spaces of work. Negotiations of the Free Trade Area of the Americas Agreement and World Trade Organization are considered.